Microbial Monitoring in the EDEN ISS greenhouse, a mobile test facility in Antarctica - Fahrion, J.; Fink, C.; Zabel, P.; Schubert, D.; Houdt, R. Van; Leys, N.; Eikmanns, B.; Beblo-Vranesevic, K.; Rettberg, P. (2019)
The EDEN ISS greenhouse, integrated in a container, is a mobile test facility in Antarctica and is used to investigate new plant cultivation techniques for future space programs. The EDEN ISS container was used from January 2018 to December 2018 for fresh food production for the overwintering crew at the Antarctic Neumayer III station.